Comparison Between Ohmic and Conventional Heating of Pineapple and Longan in Sucrose Solution - Tumpanuvatr, Titaporn; Jittanit, Weerachet; Kaewchutong, Supaporn; Jan-Ob, Orapin; Pham , Hoang; Sajjaanantakul, Tanaboon (Agriculture and Natural Resources, 2015)
Ohmic heating is an innovative thermal processing method in which an alternating electric current is directly released through food materials to generate heat. The temperature inside the food during ohmic heating can be raised rapidly and uniformly depending on the electrical conductivity of the food. In this research, the electrical conductivities of pineapple, longan and sucrose solution were measured. Furthermore, mixtures of fruit and sucrose solution at 12 °Brix were heated from 30 °C to about 90 °C by ohmic and conventional methods. The aims were to: 1) investigate the possibility of applying ohmic heating to the mixture of fruit and sucrose solution; and 2) to compare the quality of ohmically heated samples with that of conventionally heated counterparts using the same heating rate. The results indicated that the electrical conductivities of pineapple and longan were in the ranges 0.1–1.3 and 0.3–1.0 S.m-1, respectively. Moreover, it appeared from the analysis of variance that there was no significant difference in the textural attributes between ohmically and conventionally heated samples whereas the color values were significantly different. In addition, a positive effect of ohmic heating on microbial reduction was found for the pineapple pieces with the numbers of mesophilic bacteria, molds and yeast in the ohmically treated samples being significantly lower than those of conventionally heated specimens. The energy consumption was comparable between the two techniques. The findings in this work confirmed that the ohmic method could be an interesting option for heating these products.